The Role Of Green Finance In Attaining Environmental Sustainability Within ESG Performance In EU Countries - Dr. Prof. (CMA) Roop Kishore Singhal; Dr. Akanksha Taunk; Dr Aruna Deoskar; Dr. Deepika Ameta; Dr. Prof. Prashant Barge; Dr. Shekhar Verma; Dr. Prof Nalini Dixit; Mr. Anuj Goel; Dr. Sumitra Roy (The Bioscan, 2025)
This study investigates the role of green finance in advancing the environmental dimension of Environmental, Social and Governance (ESG) performance across European Union (EU) member states. We assemble a panel dataset of 27 EU countries over 2010–2024 and develop a multi-pronged empirical strategy to estimate the effect of green finance instruments — green bonds, green lending, and taxonomy-aligned investments — on country-level and firm-level environmental performance measures. Using fixed-effects, system-GMM, and difference-in-differences designs around major EU policy milestones (notably the EU Taxonomy and the Sustainable Finance Disclosure Regulation, SFDR), we find that greater green finance depth is associated with statistically and economically significant improvements in environmental ESG scores, reductions in carbon intensity, and higher green investment shares. Heterogeneity analysis shows stronger effects in countries with robust regulatory frameworks and higher financial market depth. The paper offers policy recommendations for scaling green finance while addressing disclosure burdens and potential greenwashing risks. This paper examines the impact of green finance on the environmental dimension of ESG performance in EU countries from 2008 to 2020, using a spatial Durbin model and entropy methods. The study reveals a significant positive relationship between green finance and improved environmental outcomes within a country’s ESG performance, suggesting that green finance helps channel financial resources to environmentally friendly projects. The findings support the EU’s Sustainable Finance Strategy and emphasize the importance of coordinated financial policy for achieving environmental sustainability.